2000
DOI: 10.1016/s1097-2765(00)80436-0
|View full text |Cite
|
Sign up to set email alerts
|

The RFX-Type Transcription Factor DAF-19 Regulates Sensory Neuron Cilium Formation in C. elegans

Abstract: Many types of sensory neurons contain modified cilia where sensory signal transduction occurs. We report that the C. elegans gene daf-19 encodes an RFX-type transcription factor that is expressed specifically in all ciliated sensory neurons. Loss of daf-19 function causes the absence of cilia, resulting in severe sensory defects. Several genes that function in all ciliated sensory neurons have an RFX target site in their promoters and require daf-19 function. Several other genes that function in subsets of cil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
402
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(422 citation statements)
references
References 57 publications
18
402
0
2
Order By: Relevance
“…7 A key promoter element present in a group of genes expressed in ciliated cells, the X-box, 46 was not evident in our comparative analysis of the proximal promoter. An extended search, however, showed that putative X-boxbinding sites were present within 2 kb distance of the ATG start codons in the Pkd1 genes and also in the distal promoters of the Pkd2 genes.…”
Section: Human Gtctcactcttgttgcccaggctggagtgccat---------------------mentioning
confidence: 66%
“…7 A key promoter element present in a group of genes expressed in ciliated cells, the X-box, 46 was not evident in our comparative analysis of the proximal promoter. An extended search, however, showed that putative X-boxbinding sites were present within 2 kb distance of the ATG start codons in the Pkd1 genes and also in the distal promoters of the Pkd2 genes.…”
Section: Human Gtctcactcttgttgcccaggctggagtgccat---------------------mentioning
confidence: 66%
“…Yet, there are known examples in which cis-regulatory sequences are highly conserved between C. elegans and mammalian promoters. For example, the target genes of DAF-19, an RFX-type TF, contain conserved X boxes of 13-14 bp of imperfect inverted repeats that are similar to the mammalian X boxes (Swoboda et al 2000). Shostak et al (2004) showed that most BSs of the C. elegans intracellular receptor DAF-12 contain conserved sites of the mammalian DR5 motifs (retinoic acid-responsive element) sufficient for transcriptional activation by DAF-12.…”
Section: Genome Research 79mentioning
confidence: 99%
“…1C'). Members of the Regulatory Factor X (RFX) family of winged-helix transcription factors regulate ciliogenesis in nematodes, insects, and vertebrates (Swoboda et al, 2000;Dubruille et al, 2002;Bonnafe et al, 2004). A gene knockout of Rfx3 in the mouse resulted in, among others, stunted PNC cilia and laterality defects (Bonnafe et al, 2004).…”
Section: Ciliary Gene Expressionmentioning
confidence: 99%